THE REVENUE GAP OF NON-TAX STATE REVENUE FROM SOCIAL FORESTRY IN LAMPUNG PROVINCE - Niko Ardyanto; Indra Gumay Febryano; Arief Darmawan; Christine Wulandari; Zainal Abidin (Forestry Study Program University Of Mataram, 2026)
Optimizing Non-Tax State Revenue (PNBP) from Social Forestry (SF) is important to ensure that community-based forest utilization contributes to state revenue and sustainable forest governance. This study estimated the potential, realization, and revenue gap of PNBP from SF activities in Lampung Province using a revenue gap analysis approach. A quantitative descriptive method was applied by integrating planning data from the Social Forestry Management Plan (RKPS), production data from the Forest Product Administration Information System (SIPUHH), and revenue realization data from the Non-Tax State Revenue Information System (SIPNBP). The analysis covered 138 SF groups with verified RKPS documents and recorded PNBP payments in 2025. The estimated potential PNBP reached IDR 3.71 billion, while the recorded realization was IDR 785.11 million, resulting in an estimated revenue gap of IDR 2.92 billion (78.86%). Of the 44 Non-Timber Forest Product (NTFP) commodities planned in the RKPS, only 21 were recorded in the production and payment systems, indicating a substantial discrepancy between planned and recorded activities. The revenue gap was associated with inconsistencies between planning documents and implementation, non-standard production units, limitations in data integration, and indications of under-reporting in the administrative system. These findings highlight the importance of improving planning quality, institutional capacity, data standardization, system integration, and administrative governance to optimize PNBP in SF. Since the analysis relies on administrative records rather than verified field production data, the results should be interpreted as an indicative revenue gap rather than a confirmed state revenue loss.